Dissection of vertebrate hematopoiesis using zebrafish thrombopoietin - Svoboda, Ondřej; Stachura, David L; Machoňová, Olga; Pajer, Petr; Brynda, Jiří; Zon, Leonard I; Traver, David; Bartůněk, Petr (Blood, 2014)
In nonmammalian vertebrates, the functional units of hemostasis are thrombocytes. Thrombocytes are thought to arise from bipotent thrombocytic/erythroid progenitors (TEPs). TEPs have been experimentally demonstrated in avian models of hematopoiesis, and mammals possess functional equivalents known as megakaryocyte/erythroid progenitors (MEPs). However, the presence of TEPs in teleosts has only been speculated. To identify and prospectively isolate TEPs, we identified, cloned, and generated recombinant zebrafish thrombopoietin (Tpo). Tpo mRNA expanded itga2b:GFP(+) (cd41:GFP(+)) thrombocytes as well as hematopoietic stem and progenitor cells (HSPCs) in the zebrafish embryo. Utilizing Tpo in clonal methylcellulose assays, we describe for the first time the prospective isolation and characterization of TEPs from transgenic zebrafish. Combinatorial use of zebrafish Tpo, erythropoietin, and granulocyte colony stimulating factor (Gcsf) allowed the investigation of HSPCs responsible for erythro-, myelo-, and thrombo-poietic differentiation. Utilizing these assays allowed the visualization and differentiation of hematopoietic progenitors ex vivo in real-time with time-lapse and high-throughput microscopy, allowing analyses of their clonogenic and proliferative capacity. These studies indicate that the functional role of Tpo in the differentiation of thrombocytes from HSPCs is well conserved among vertebrate organisms, positing the zebrafish as an excellent model to investigate diseases caused by dysregulated erythro- and thrombo-poietic differentiation.
Keywords: embryo nesavčí; kultivované buňky; Cells, Cultured; Cell Proliferation; dánio pruhované; thrombopoetin; Animals; proliferace buněk; Cell Differentiation; geneticky modifikovaná zvířata; trombocyty; hematopoetické kmenové buňky; zvířata; hematopoéza; Hematopoietic Stem Cells; Zebrafish; buněčná diferenciace; Thrombopoietin; Embryo, Nonmammalian; Hematopoiesis; Animals, Genetically Modified; Blood Platelets